2017
DOI: 10.1371/journal.pone.0188370
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response against two surface antigens of Chlamydia pecorum in vaccinated and naturally infected sheep

Abstract: Chlamydia pecorum is a globally recognised livestock pathogen due to the significant clinical and economic impact it poses to livestock producers. Routine serological diagnosis is through a complement fixation test (CFT), which is often criticised for cross-reactivity, poor sensitivity and specificity. Although serology remains the preferred method in veterinary diagnostic laboratories, serological assays based on surface antigens of C. pecorum have not been established until now. In this study, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this study, we also identified three lambs that were qPCR positive (2/3 lambs were repeatedly qPCR positive) but had no detectable CFT antibodies longitudinally. In our previous study on characterisation of humoral immune responses to naturally occurring C. pecorum infections we have identified moderate antigen specific MOMP and PmpG IgG antibodies present in these three lambs longitudinally ( Bommana et al, 2017 ). These findings elude us to believe that these animals are not passive shedders of C. pecorum and that in reality CFT as an assay has relatively poor sensitivity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, we also identified three lambs that were qPCR positive (2/3 lambs were repeatedly qPCR positive) but had no detectable CFT antibodies longitudinally. In our previous study on characterisation of humoral immune responses to naturally occurring C. pecorum infections we have identified moderate antigen specific MOMP and PmpG IgG antibodies present in these three lambs longitudinally ( Bommana et al, 2017 ). These findings elude us to believe that these animals are not passive shedders of C. pecorum and that in reality CFT as an assay has relatively poor sensitivity.…”
Section: Discussionmentioning
confidence: 84%
“…CFT is inappropriate for the retrospective diagnosis of chlamydial mucosal infections, such as in oculo-genital sites that make antibodies specific to a localised site of infection ( Barnes, 1989 ; Griffiths et al, 1996 ). The exception to this is diagnosis of chlamydial polyarthritis or abortion in ruminants, wherein high exposure to Chlamydia elicits a pronounced systemic increase in antibody levels ( Perez-Martinez, Schmeer & Storz, 1986 ; Bommana et al, 2017 ). Potentially, there may exist early seroconversion or antibody markers for improved serological diagnosis of acute-phase infection in livestock, overcoming the shortcomings of CFT.…”
Section: Discussionmentioning
confidence: 99%
“…These 35 sheep were selected following 2 rounds of prescreening for Chlamydia in over 100 sheep, collecting rectal swabs for testing by C. pecorum-specific qPCR (qualitative polymerase chain reaction) as well as blood samples for complement fixation test. 4 Both tests confirmed Chlamydia-negative status in the 35 animals selected for experimental studies. The objectives of the previous study 21 were to (1) establish an infection model of chlamydial arthritis, (2) determine the optimal delivery route, (3) identify potential differences between C. pecorum isolates IPA and E58 in vivo, and (4) observe both infection and recovery phases following infection.…”
Section: Experimental Design and Samplingmentioning
confidence: 80%
“…Peptide ELISA’s were performed to determine the antibody response to P1 and P2, as described by Bommana et al . (2017) [ 37 ] with the following modifications. Streptavidin plates were initially coated with either, 1.5μg/well of P1 or 1.5μg/well of P2.…”
Section: Methodsmentioning
confidence: 99%